Control of adult stem cells in vivo by a dynamic physiological environment: diet-dependent systemic factors in Drosophila and beyond - Ables, Elizabeth T. (2012)
Adult stem cells are inextricably linked to whole-body physiology and nutrient availability through complex systemic signaling networks. A full understanding of how stem cells sense and respond to dietary fluctuations will require identifying key systemic mediators, as well as elucidating how they are regulated and integrated with local and intrinsic factors across multiple tissues. Studies focused on the Drosophila germline have generated valuable insights into how stem cells are controlled by diet-dependent pathways, and increasing evidence suggests that diverse adult stem cell populations respond to nutrients through similar mechanisms. Systemic signals, including nutrients themselves and diet-regulated hormones such as Insulin/Insulin-like growth factor or steroid hormones, can directly or indirectly affect stem cell behavior by modifying local cell-cell communication or intrinsic factors. The physiological regulation of stem cells in response to nutritional status not only is a fascinating biological problem, but also has clinical implications, as research in this field holds the key to non-invasive approaches for manipulating stem cells in vivo. In addition, given the known associations between diet, stem cells, and cancer risk, this research may inspire novel anti-cancer therapies.